Pemberdayaan Kelompok Tani dalam Pengembangan Varietas Unggulan Guna Mendukung Ketahanan Pangan Daerah Perbatasan - Japo Alberto; Linda Wahyuni; Septiana Septiana; Deffrinica Deffrinica; Dedy Dedy; Aloysius Hari Kristianto (Journal of Creative Student Research, 2026)
Border regions play a strategic role in maintaining national sovereignty and food security; however, their agricultural sector continues to face structural limitations, including weak institutional capacity of farmer groups, limited access to superior seed varieties, and insufficient technological extension services. These conditions contribute to low agricultural productivity, high vulnerability to climate change, and unstable food availability for border communities. This study aims to analyse the institutional capacity of farmer groups, identify the potential and constraints in developing locally-based superior varieties, and formulate an effective and contextual empowerment model to support food security in the border area of Bengkayang Regency. A mixed-methods approach with participatory design was employed, combining quantitative descriptive analysis and qualitative exploration. Data were collected through structured questionnaires, in-depth interviews, and Focus Group Discussions (FGDs), and were analysed using SWOT analysis with IFAS and EFAS matrices. The results indicate that farmer groups possess relatively strong internal conditions (IFAS score = 2.489) and highly supportive external conditions (EFAS score = 3.207), positioning them in Quadrant I and recommending an aggressive S–O strategy. The principal strategies formulated include the collective adoption of superior varieties, the development of group-based demonstration plots, and the strengthening of group administrators as technology adoption facilitators. This study contributes to the development of a participatory empowerment framework grounded in local potential, which can be adapted to sustainably strengthen food security in border regions.